Home range patterns of Helmeted Woodpecker (Celeus galeatus), Lineated Woodpecker (Dryocopus lineatus), and Robust Woodpecker (Campephilus robustus) in Misiones, Argentina, in a global perspective - Lammertink, J. Martjan (2022)
Home range mapping studies of birds inform about area requirements and responses to land management as reflected by home range sizes and by resource selection within home ranges. Tracking studies of woodpeckers (Picidae) so far have been concentrated in temperate regions. In the subtropical Atlantic Forest of northeast Argentina, we assessed interspecific differences in home range sizes in old-growth forests and selectively logged forests of Helmeted Woodpecker (Celeus galeatus, a globally threatened species), Lineated Woodpecker (Dryocopus lineatus), and Robust Woodpecker (Campephilus robustus). Helmeted Woodpecker had larger breeding home ranges in selectively logged forests, averaging 105 ± 39 ha for pairs, versus 60 ± 13 ha in old-growth forests. Lineated Woodpecker breeding home ranges of pairs averaged 56 ± 22 ha, and those of Robust Woodpecker 43 ± 22 ha, with no differences between forest types. Helmeted Woodpeckers had an unusual separation between the home ranges of males and females in breeding pairs, with a mean area overlap of only 8% ± 9% near the nest tree, resulting in large home ranges for pairs. Helmeted Woodpecker and Robust Woodpecker individuals that were followed into the post-breeding stage had marked expansions of their home range sizes relative to breeding home ranges. To place our findings with Atlantic Forest woodpeckers in perspective we reviewed whether woodpecker home range sizes increase with latitude and body mass globally. For 29 populations of 22 woodpecker species, a power regression model with these factors explained 24.1% of variation in breeding home range sizes, with 17.1% of variation explained by latitude alone. Woodpecker species with larger home ranges than predicted values were three species of North American woodpeckers of coniferous forests, as well as the Helmeted Woodpecker. Our results of smaller home ranges in old-growth forests for the Helmeted Woodpecker affirm an association of this species with such forests. We urge the conservation of the few remaining tracts of old-growth Atlantic Forest and more restoration of logged forests to mature conditions.